Gender Studies in Islam (2000–2025): Research Fronts, Hotspots, and Conceptual Shifts in the Literature - Judijanto, Loso (West Science Islamic Studies, 2026)
In this article, the world research front in the area of gender studies in Islam is considered for the period from 2000 to 2025. Bibliometric and network analysis methods have been used for exploring author collaborations, citation patterns, and keyword relations. In result, it was found that this research network has a complex structure, including significant participation of countries like the US and the UK, as well as developing involvement of Muslim countries such as Malaysia, Turkey, and Indonesia. Citation analysis revealed the most influential literature and themes, including themes on veiling, identity, Islamophobia, and socio-political aspects of gender. Keyword analysis showed that the key concepts included "Islam" and "religion," with other concepts developing in time, like feminism, psychology, culture, and gender identity. Overlay visualization showed that the current state of the research area is dominated by interdisciplinary studies focused on critical analysis rather than initial demographic and statistical approaches. Density map confirmed the importance of the identified topics but also indicated emerging research fronts. In sum, the analysis showed the development of gender studies in Islam from an underdeveloped subject into a multidisciplinary field with significant expansion of concepts and methodologies and international collaboration.